2022
DOI: 10.1186/s13023-022-02198-9
|View full text |Cite
|
Sign up to set email alerts
|

Is physical activity a future therapy for patients with Marfan syndrome?

Abstract: Introduction The international recommendations tend to avoid physical activity (PA) for patients with Marfan syndrome (MFS). However, exceptions have recently been made in the most recent recommendations for these patients, suggesting benefits from doing PA at low intensity only. Furthermore, there is no evidence that moderate aerobic or weight training can worsen the disease symptoms and increase mortality of MFS patients. The present review sums up the work carried out in the field of PA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Transgenic mouse models of MFS reported that moderate dynamic exercise mitigated the progression of cardiovascular phenotypes associated with MFS [ 8 , 9 ]. Regular physical activity reduced cardiovascular risks in the general population and in patients with cardiovascular diseases and other chronic childhood conditions [ 12 ]. Furthermore, children with MFS reported about the adverse impact of systemic manifestations, such as musculoskeletal problems, on their physical activities [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic mouse models of MFS reported that moderate dynamic exercise mitigated the progression of cardiovascular phenotypes associated with MFS [ 8 , 9 ]. Regular physical activity reduced cardiovascular risks in the general population and in patients with cardiovascular diseases and other chronic childhood conditions [ 12 ]. Furthermore, children with MFS reported about the adverse impact of systemic manifestations, such as musculoskeletal problems, on their physical activities [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, reviews on pediatric cardiac rehabilitation [ 10 ] and obesity in children [ 11 ] reported improved physical fitness following rehabilitation exercise programs. Moreover, the benefits of regular physical activity are well-established, particularly in reducing cardiovascular risks in both the general population and patients with cardiovascular, as well as other chronic diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regimen of mild PA appears to have beneficial effects. Cardiorespiratory and muscular endurance are improved as a result of physical exercise [14]. The MFS must continue to be active in order to maintain their physical health.…”
Section: Physical Rehabilitationmentioning
confidence: 99%
“…En raison de ces directives appelant à la prudence, la prescription de l'exercice chez ces patient-e-s est difficile à mettre en place, surtout en l'absence de programme d'entraînements clairement établis. 6 Pourtant, la sédentarité et l'inactivité physique qui en découlent augmentent le risque de complications vasculaires, notamment le risque de développer/péjorer une hypertension artérielle. Cette dernière augmente le risque de rupture d'anévrisme aortique chez les patient-e-s avec syndrome de Marfan par exemple.…”
Section: Exercice Physique Pour Les Maladies Vasculaires Raresunclassified
“…Les rares études sur l'exercice et le syndrome de Marfan montrent globalement un effet favorable de l'entraînement, notamment sur la capacité cardiorespiratoire et musculaire. 6 Il en résulte que la sédentarité fait partie des facteurs de risque cardiovasculaire dont il faut activement s'occuper chez ces patient-e-s. Les activités d'intensité légère/ modérée, pratiquées de manière régulière, comme la marche, la randonnée, la natation ou le vélo sont à favoriser. Pour être sûr de se trouver dans cette fourchette d'intensités sécuritaires, il faut pouvoir parler avec aisance pendant l'effort, sans devoir s'arrêter pour reprendre son souffle.…”
Section: Exercice Physique Pour Les Maladies Vasculaires Raresunclassified